Priority-based approach to mitigate selfish misbehaviour in delay tolerant network. (25th January 2021) - Patel, Ashish; Bhadra, Dhwani
Delay tolerant networks (DTNs) is a solution to challenged networks which suffer from intermittent connectivity or high delay, thereby offering delay-tolerant support. DTN focuses on minimising delay and maximising forwarding and delivery ratio of data packets. DTN follows the store-carry-forward mechanism where a message is sent to the closest node using a store-carry-forward mechanism. Due to limited resources, poor connectivity and no centralised control, DTN is vulnerable to various attacks. These circumstances lead to the misbehaviour of network nodes and degrade the performance of the system. In this paper, first, we present a comprehensive review of the performance and security of DTN to identify 16 critical parameters allied to similar opportunistic networks. In the second phase of the article, the problem of node misbehaviour in DTN is analysed, and a novel priority-based approach to mitigate selfish misbehaviour is proposed. The acclaimed approach is validated using ONE simulator and exhibits improved results.